Modelo de gestión contable – financiera para la finca agrícola dos hermanos, del recinto la familia, cantón Valencia provincia de Los Ríos, año 2017 - Sánchez Moreira, Belén Marilyn (2017)
The present research had as objective to determine a models of Financial Accounting Management for the farm two brothers, of the enclosure the family, Canton Valencia Province of the Rivers, year 2017, the main reason that I took to this investigation was to put into practice by at least the basic principles of an accounting management in the aforementioned property. Being a type of research descriptive and applied to reality, we used the inductive and descriptive methods for the development of research, evidently everything with the support of all sources of primary and secondary information. The work began with a description of the current situation of the farm, evidencing the aforementioned with a survey made to the workers of the same, which obtained the information necessary and sufficient for the objectives proposed in this research. The data were then tabulated and analyzed in percentage terms, determining that most of them stated that the farm under study has no accounting management and that everything is empirically carried through invoices or sales notes and has no basic knowledge of the work that are making In addition, little or no knowledge of the administrative and accounting phases of the owners of the farm was evident, which has contributed to the total lack of knowledge of the income and monetary outflows that the property generates. In such a way that the general analysis of the results obtained concludes that it is necessary that the representative of the farm implement accounting management models at least the basics that is designed and consists of this research.